PENERAPAN METODA PERAMALAN UNTUK MENETAPKAN MPS DAN MRP PADA STRIPER BUSHING (STUDI KASUS DI RUANG PRODUKSI UNIT STRIPER BUSHING PADA CV. SURYA BAJA MANDIRI KARAWANG) - Ade Suhara (Industry Xplore, 2020)
Company CV. Surya Baja Mandiri is a service company in the form of a privately owned workshop that produces spare parts products, especially automotive, most of whose products are ordered directly from abroad, namely Japan, for example for the production of Stripper Bushing. To fulfill quality orders and on time according to the order schedule (Due Date) in order to maintain the satisfaction of the company that is the producer and still get efficient results for the company, a production schedule for the supply of materials that is truly effective is needed. To determine a production schedule and supply of materials that are truly effective, the author begins by doing a forecast using the company's past demand data starting from May 2020 to April 2020 which is an average of 8000 pcs per month. The Holt forecasting method was chosen because it gives the smallest MSE value of 28113.96 compared to the Brown forecasting method 741098966 and the Trend Linear forecasting method 2381480.62